HUBUNGAN PEMAHAMAN PESERTA DIDIK TENTANG NEGARA KESATUAN REPUBLIK INDONESIA DENGAN SIKAP BELA NEGARA - NANDA LEGA JAYA PUTRA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The purpose of this study was to obtain empirical data about the relationship between students' understanding of the Unitary Republic of Indonesia (Unitary State of the Republic of Indonesia) and the state defense attitude at SMK Al-Bahri Bantar Gebang. This research was conducted on grade X students of Al-Bahri Bantar Gebang Vocational School. The research method used was quantitative descriptive method with correlation study approach. The sample in this study was taken randomly using the Proportional Random Sampling technique with a sample size of 40 respondents. The instrument used was a multiple choice test for variable X and a questionnaire with the type of attitude scale for variable Y. The reliability test results for variable X were 0.968 (0.968> 0.444) and Y variable were 0.965 (0.965> 0.444). Hypothesis testing is done using Pearson's product moment formula. Obtained r count 0.656 with r table 0.312 (0.656> 0.312). Thus it can be concluded that there is a positive relationship between students' understanding of the Homeland with the attitude of defending the country.